2014
DOI: 10.3233/nre-141153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-action observation on standing balance learning: A change of brain activity detected using functional near-infrared spectroscopy

Abstract: BACKGROUND: Studies suggest that the observation of others' actions leads to enhanced motor skill learning. OBJECTIVE: We examined whether others' or self-action observation is effective for standing balance learning. In addition, we examined cortical activation during action observation using functional near-infrared spectroscopy. METHODS: Thirty-nine healthy young subjects were assigned randomly to the Control, Other-Observation (O-O), and Self-Observation (S-O) groups. The subjects learned to stand on a til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Measures of neurophysiology respond in a predictable manner to cognitive demand/mental workload or mental effort (Gevins and Smith, 2003;Antonenko et al, 2010;Setz et al, 2010;Ayaz et al, 2012;Brouwer et al, 2012;Borghini et al, 2014;Hogervorst et al, 2014;Reiner and Gelfeld, 2014;Gable et al, 2015;Charles and Nixon, 2019). As mental effort increases, sympathetic activation increases and parasympathetic inhibition decreases (Berntson et al, 1991), paralleled by changes in the central nervous system such as in oscillations in the EEG signal with alpha oscillations generally increasing and theta oscillations generally decreasing with decreasing demands (Klimesch, 1999;Klimesch et al, 2005;Antonenko et al, 2010;Brouwer et al, 2012) and in activation patterns in the fNIRS signal with activity in the (pre)frontal cortex generally increasing (Ayaz et al, 2012;Hiyamizu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of neurophysiology respond in a predictable manner to cognitive demand/mental workload or mental effort (Gevins and Smith, 2003;Antonenko et al, 2010;Setz et al, 2010;Ayaz et al, 2012;Brouwer et al, 2012;Borghini et al, 2014;Hogervorst et al, 2014;Reiner and Gelfeld, 2014;Gable et al, 2015;Charles and Nixon, 2019). As mental effort increases, sympathetic activation increases and parasympathetic inhibition decreases (Berntson et al, 1991), paralleled by changes in the central nervous system such as in oscillations in the EEG signal with alpha oscillations generally increasing and theta oscillations generally decreasing with decreasing demands (Klimesch, 1999;Klimesch et al, 2005;Antonenko et al, 2010;Brouwer et al, 2012) and in activation patterns in the fNIRS signal with activity in the (pre)frontal cortex generally increasing (Ayaz et al, 2012;Hiyamizu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while the current study only examined PFC activity, changes during visuomotor learning have also been reported with fNIRS in other brain areas, such as the supplementary motor area and the pre-supplementary motor area (Hatakenaka et al 2007;Sagari et al 2015) and the sensory-motor cortex (Hatakenaka et al 2007;Hiyamizu et al 2014;Ikegami and Taga 2008;Sagari et al 2015). Effects of visuomotor learning on brain activity are not only reflected in reduced activity suggesting a decrease in the cognitive effort; enhanced brain activity during learning has also been demonstrated.…”
Section: Discussionmentioning
confidence: 52%
“…In another study, the participants were divided into a self-observation followed by physical training group, a physical training after observing healthy adults’ motions group, and a physical training without observation group. The three groups underwent balance training on a horizontal surface, and the results showed that the self-observation group showed a significant improvement of balance 16 ) . The results of the present study were consistent with those of the abovementioned prior study, self-observation training improves the asymmetric gait pattern.…”
Section: Discussionmentioning
confidence: 99%